Employment Determination in Enterprises under Communism and in Transition : Evidence from Central Europe - Swati Basu; Saul Estrin; Jan Svejnar (Institute for the Study of Labor (IZA), 2004)
In this paper, we present a comparative analysis of employment determination in four transition economies as they move from central planning to a market economy in the early 1990s. We use firm level panel data sets from the Czech Republic, Hungary, Poland and Slovakia to estimate dynamic employment equations for the period immediately before and after the start of transition. We find evidence that firms behave for the most part as if they were on their labor demand curves, with little evidence of labor hoarding. There were significant cross-country variations in the determinants of employment during the reform process however. Hungarian and Polish firms started the transition already substantially reformed, and became even more responsive to market signals as transition proceeded. In contrast, firms in the Czech and Slovak republics started in the completely unresponsive mode characteristic of central planning, but rapidly caught up with their counterparts in Hungary and Poland.
Keywords: J23; J66; J50; 330; employment determination; transition economies; Arbeitsnachfrage; Beschäftigung; Arbeitsmarkt; Übergangswirtschaft; Schätzung; Tschechische Republik; Ungarn; Polen; Slowakei